Interlogue : a museum engagement toolkit to promote intergenerational relationships between grandparents and grandchildren - Tay, Yu Qing (Nanyang Technological University, 2020)
Intergenerational interaction in Singapore has become increasingly limited due to changing family structure. Interlogue project aims to strengthen relationships between grandparents and grandchildren of Singapore today through intergenerational sharing. The National Gallery Singapore (NGS) collection was utilised in this programme as conversation starters for participants due to its national narrative that is relatable to most participants. Children aged 6 to 9 years old and their grandparents were also engaged to provide feedbacks on the programme content in order to ensure activities and content were designed to suit both generations. In doing so, it explored the potential for museum spaces to hold intergenerational engagement activities. This facilitated museum programme sparks dialogue between grandparents and grandchildren, through museum artefacts, to encourage meaningful interaction between the two generations beyond the realm of their homes. This programme utilises a kit that includes an activity book accompanied with objects to prompt engagement and document their sharing.